Exceptional children : an introduction to special education - Heward, William L.; Quijano, Yolanda S.;Capulong, Yolanda T. (Upper Saddle River, New Jersey : Pearson Education/Merrill/Prentice Hall, 2006)
Special education is an ongoing story of people. It is the story of a intervention services. It is the story of a child with mental retardation whose parents and teachers work together to ensure she participates in classroom and extracurricular activities with her peers. It is the story of a middle school student with learning disabilities who helps his parents and teachers plan an instructional program that builds upon his strengths and addresses his weaknesses. It is the story of the gifted and talented child who brings new insights to old problems, the high school student with cerebral palsy who is learning English as his second language, and the young woman with visual impairments who has recently moved into her own apartment and rides a city bus to work. Special education is also the story of the parents and families of exceptional children and of the teachers and other professionals who work with them.
Part I. Special education in the Philippines -- Part II. The Essential concepts of special education -- Part III. Children and youth with special education needs.
Includes bibliographical references and index.
Keywords: GIFTED CHILDREN -- EDUCATION -- PHILIPPINES